Authority, autonomy and the first London Bills of Mortality. (27th July 2020) - Heitman, Kristin
Abstract: Publication of population‐level data can help balance a government's need for authority with individual residents' practical need for autonomy, even during the chaos and urgency of an epidemic. Starting in the early 16th century, efforts to track the spread of epidemic plague across England and Wales included royal orders to compile weekly, parish‐by‐parish mortality reports. The City of London devised a novel, quantitative response: rather than producing lists of plague victims, its parishes counted up those who had died of plague and the total number buried that week to yield a local relative frequency of plague deaths. Initially, in keeping with common practices, these data were available only to London's Lord Mayor and aldermen, the sovereign, and the Privy Council. But during the plague of 1592, the City of London's printer posted large‐format printed versions of each week's report in public places throughout the City, thus providing free, general access to the week's mortality data. These were the first London Bills of Mortality. Thanks to London's high numeracy rate, many residents could not only read numbers but use tables and interpret ratios. Even those with minimal numeracy could participate in discussions of the data and integrate the results into their lived experience, potentially assessing risks more accurately and making better choices. The fundamental concerns faced by London's government and residents in the 16th century are remarkably similar to those now raised by COVID‐19. The broad requirements for and potential advantages of sharing a stream of useful, reliable statistical data with a numerate public also run in parallel.